2021
DOI: 10.7759/cureus.14347
|View full text |Cite
|
Sign up to set email alerts
|

Metaplastic Breast Carcinoma: Clinicopathological Parameters and Prognostic Profile

Abstract: IntroductionMetaplastic breast carcinoma (MBC) is defined as breast cancer with a heterologous non-glandular component. MBC is considered a special type of breast cancer with a prognosis that is worse than invasive ductal carcinoma (IDC) of the breast. MBC is the most common breast cancer with a triple-negative profile. Therefore, in this study, we evaluated the clinicopathological parameters, recurrence and survival of MBC in our population. MethodsWe conducted a retrospective observational study in the Depar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 21 publications
(28 reference statements)
0
5
0
Order By: Relevance
“…Breast cancer was divided into luminal A (ER/PR positive, Her-2 negative with low Ki-67 index) disease, luminal B (ER/PR positive, Her-2 negative with high Ki-67 index, or ER/PR positive and Her-2 positive) disease, Her-2 positive (ER and PR negative and Her-2 positive) disease, and triple-negative (ER, PR, and Her-2 negative) disease according to molecular subtyping. MBC: metaplastic breast carcinoma; NSIBC: nonspecific invasive breast carcinoma; ER: estrogen receptor; PR: progesterone receptor; Her-2: human epidermal growth factor receptor 2. e Breast Journal 3 is poorly differentiated and greatly aggressive [10]. Previous studies showed that MBC mainly metastasized via the lymphatics and blood, and early hematogenous metastasis often involved the lung and the bone, especially in metaplastic carcinoma with mesenchymal differentiation [11].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Breast cancer was divided into luminal A (ER/PR positive, Her-2 negative with low Ki-67 index) disease, luminal B (ER/PR positive, Her-2 negative with high Ki-67 index, or ER/PR positive and Her-2 positive) disease, Her-2 positive (ER and PR negative and Her-2 positive) disease, and triple-negative (ER, PR, and Her-2 negative) disease according to molecular subtyping. MBC: metaplastic breast carcinoma; NSIBC: nonspecific invasive breast carcinoma; ER: estrogen receptor; PR: progesterone receptor; Her-2: human epidermal growth factor receptor 2. e Breast Journal 3 is poorly differentiated and greatly aggressive [10]. Previous studies showed that MBC mainly metastasized via the lymphatics and blood, and early hematogenous metastasis often involved the lung and the bone, especially in metaplastic carcinoma with mesenchymal differentiation [11].…”
Section: Discussionmentioning
confidence: 99%
“…In our study, a total of 34 patients with MBC were able to obtain complete pathological diagnoses, including 17 cases (50.00%) of squamous cell carcinoma, 1 case (2.94%) of spindle cell carcinoma, 11 cases (32.35%) of carcinoma with mesenchymal differentiation, 4 cases (11.76%) of mixed metaplastic carcinoma, and 1 case (2.94%) of fibromatosis-like metaplastic carcinoma. As for biological behavior, MBC is poorly differentiated and greatly aggressive [ 10 ]. Previous studies showed that MBC mainly metastasized via the lymphatics and blood, and early hematogenous metastasis often involved the lung and the bone, especially in metaplastic carcinoma with mesenchymal differentiation [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…5,7) Most tumors are triple negative (85%), and the most common age group is between 36 and 50 years. 7,8) They tend to be large in size, and most cases are grade 3. 8) One-third of patients have metastatic disease at initial presentation.…”
Section: T He Diagnosis Of St Elevation Myocardial Infarction (Stemi)...mentioning
confidence: 99%
“…Metaplastic breast carcinoma (MBC) is one of the rare special subtypes of breast carcinoma associated with poor prognostic features compared with invasive breast ductal carcinoma [ 1 , 2 ]. These tumors tend to have a large tumor size at the time of presentation, and, therefore, require neoadjuvant chemotherapy [ 3 ].…”
Section: Introductionmentioning
confidence: 99%